2018
DOI: 10.1002/jcsm.12349
|View full text |Cite
|
Sign up to set email alerts
|

Poor performance of psoas muscle index for identification of patients with higher waitlist mortality risk in cirrhosis

Abstract: BackgroundSarcopenia, characterized by low muscle mass, associates with mortality in patients with cirrhosis. Skeletal muscle area in a single computed tomography image at the level of the third lumbar vertebrate (L3) is a valid representative of whole body muscle mass. Controversy remains regarding applicability of psoas muscle to identify patients at greater risk of mortality. We aimed to determine psoas muscle index (PMI) association with skeletal muscle index (SMI) and to evaluate the capacity of PMI to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 39 publications
3
100
3
Order By: Relevance
“…Our use of a contemporaneous group of age‐matched subjects without documented disorders that alter muscle mass showed that the standardized rate of muscle loss (either absolute or percentage) in cirrhosis of any aetiology is significantly greater than that due to age alone. Unlike earlier reports, in the present study we observed that all three muscle groups studied had similar predictive value for outcomes. We therefore believe that the psoas muscle area alone can be used as an indicator of muscle mass due to the ease of measurement.…”
Section: Discussioncontrasting
confidence: 73%
“…Our use of a contemporaneous group of age‐matched subjects without documented disorders that alter muscle mass showed that the standardized rate of muscle loss (either absolute or percentage) in cirrhosis of any aetiology is significantly greater than that due to age alone. Unlike earlier reports, in the present study we observed that all three muscle groups studied had similar predictive value for outcomes. We therefore believe that the psoas muscle area alone can be used as an indicator of muscle mass due to the ease of measurement.…”
Section: Discussioncontrasting
confidence: 73%
“…However, others have used L4 as a landmark . Furthermore, other studies have cited SMM area as a more complete measure than PMA alone because it is closely related to total body protein and wait‐list mortality . PMT as an alternative indicator to assess for sarcopenia has also been proposed, but it requires further validation .…”
Section: Discussionmentioning
confidence: 99%
“…(47) Furthermore, other studies have cited SMM area as a more complete measure than PMA alone because it is closely related to total body protein and wait-list mortality. (48,49) PMT as an alternative indicator to assess for sarcopenia has also been proposed, but it requires further validation. (32) Use of cross-sectional CT/MRI, segmental DEXA using appendicular measures, and phase angle BIA have been shown to be less influenced by overhydration than whole body measures.…”
Section: Discussionmentioning
confidence: 99%
“…Several key questions remain regarding the use of CT-based estimation of skeletal muscle mass, including the use of values below specific percentiles (i.e., 5th percentile) of age-and sex-matched population or optimal cut-points for mortality discrimination, sensitivity of changes over time, and the validity of measurement of psoas alone versus the total muscle area. (21)…”
Section: • Nutritional Assessment By Royal Freementioning
confidence: 99%
“…In addition, low PMI identifies an incomplete subset of patients at increased risk of mortality indicated by low SMI. (21) Although sarcopenia has classically been associated with increased mortality in both men and women with cirrhosis, emerging evidence suggests that sarcopenia is associated with disproportionately higher rates of mortality in men as compared with women. (27) This emphasizes the importance of survival analysis stratification by sex rather than simply adjusting multivariable models for sex.…”
Section: Defining Sarcopeniamentioning
confidence: 99%